Formulation of Alpha Tocopherol Acetate as a Powder Dosage Form by Adsorption - Zena A. Abdulhameed; Yehia I. Khalil (College of Pharmacy University of Baghdad, 2017)
Alpha-tocopherol acetate is one of the most important vitamin E derivatives,that were used  as antioxidants. Adsorbents like kaolin, magnesium carbonate, and microcrystalline cellulose were used successfully to incorporate oily alpha-tocopherol acetate into an acceptable powder dosage form. The results revealed that microcrystalline cellulose as an adsorbents gave the best results with 50% loading capacity at time, 8 minutes before and after incubation period (3 months at 30CÂ°), while kaolin and magnesium carbonate have been shown a significant difference before and after incubation. Addition of 1% w/w magnesium carbonate to the kaolin enhanced the loading capacity by decreasing the time of adsorption from 20 to 6 minutes and 47 to 9 minutes before and after incubation respectively. The study indicated that the best adsorbent to be used in case of oral vitamin E toxicity is microcrystalline cellulose while magnesium carbonate could be used in the formulation for their best adsorption effect. Key words :  Adsorption , Tocopherol  Acetate powder